2018
DOI: 10.1021/acsomega.8b00540
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Robust, Flame-Retardant Poly(lactic acid) Biocomposites via Combining Cellulose Nanofibers and Ammonium Polyphosphate

Abstract: Expanding the application range of flame-retardant polymer biocomposites remains a huge challenge for a sustainable society. Despite largely enhanced flame retardancy, until now the resultant poly(lactic acid) (PLA) composites still suffer reduced tensile strength and impact toughness due to improper material design strategies. We, herein, demonstrate the design of a green flame retardant additive (ammonium polyphosphate (APP)@cellulose nanofiber (CNF)) via using the cellulose nanofibers (CNFs) as the green mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 37 publications
0
76
0
Order By: Relevance
“…Yang et al incorporated benzene tricarboxylic acid grafted multiwalled carbon nanotubes (BTC‐MWCNTs) into EP thermosets, and the TC value reached 0.96 Wm −1 K −1 when 5 wt% BTC‐MWCNTs was required. In comparison with the reported works, the prepared MF‐APP exhibited much higher thermal conductive efficiency for EP thermosets.…”
Section: Resultsmentioning
confidence: 50%
“…Yang et al incorporated benzene tricarboxylic acid grafted multiwalled carbon nanotubes (BTC‐MWCNTs) into EP thermosets, and the TC value reached 0.96 Wm −1 K −1 when 5 wt% BTC‐MWCNTs was required. In comparison with the reported works, the prepared MF‐APP exhibited much higher thermal conductive efficiency for EP thermosets.…”
Section: Resultsmentioning
confidence: 50%
“…Such unsuitable IFR quality dramatically decreases the toughness of the matrix, significantly limiting its application. Some strategieshave been successfully employed for improving the tensile toughness of polymer/IFR blends to some extent, but they have provided only limited improvement in the impact strength.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks appeared at 1632 and 1400 cm −1 , which was corresponded to the stretching vibrations of aromatic compounds and CN . Besides, the peak appearing at 1130, 990, and 880 cm −1 was assigned to the stretching vibrations of POC and POP and the bending vibration of PO, respectively . It was concluded that the flame‐retardant elements such as P and N were retained in the char residue with the incorporation of PPAP.…”
Section: Resultsmentioning
confidence: 94%